ANALISIS KEBUTUHAN TAMU YANG MENGINAP TENTANG FASILITAS KAMAR DI HOSPITALTY CENTER - wita oktavia (JURNAL PENDIDIKAN DAN KELUARGA, 2018)
This type ofmresearch is descriptive research with quantitative data. The population of this study were individual and group guests staying at the Central Hospital. The sampling technique is non probability sampling, using purposive sampling. The number of samples in this study ruled 65 people. Data collection techniques were carried out using a questionnaire (questionnaire) using a Likert scale that has been tested for validity and reliability. Furthermore, the data were analyzed by quantitativepdescriptive. The result of this research is that this research has found about the guest needs about room facilities at the Hospital Center based on the data analysis above which is described by indicators. Based on the results of a study of 65 samples, the variable of room facilities needs can be categorized as very needed 74%. Then in the bedroom rankings can be categorized very needed 72%, indicators of linen items can be categorized very needed 75%, bathroom indicators can be categorized very needed 80%. Keywords: Room Facilities Needs, Hospitalty Center